Relevansi Perencanaan dan Proses Pembelajaran - Nasikhah, Umi (ILJ: Islamic Learning Journal, 2025)
A teacher is required to master the subject matter to be delivered to students and be able to deliver the subject matter effectively and efficiently. In order for teachers to carry out their duties well, they need experience and knowledge of student characters, how to deliver good material, use of media and effective learning. For this reason, a teacher must explore the ability to present interesting, organised and effective subject matter. This is an integrated part of a teacher's teaching performance for all types and levels of education. This research uses the literature method, with documentary data collection and analysis using content analysis. The results show that the teacher's performance in teaching is related to his ability to explain the content of the lesson, deal with students, help solve problems, manage the class, arrange teaching materials, determine class activities, arrange learning evaluations, determine methods, media, or even answer questions properly and wisely. To be able to carry out matters related to teaching performance, educators need to prepare lesson plans. The lesson plan is not only a formal document, but also an important instrument in ensuring the smooth and effective achievement of learning objectives.